A 1-MV low-jitter high-reliability multi-stage equal breakdown probability gas switch. (1st January 2023) - Shang, Wei; Su, Jiancang; Zeng, Bo; Gao, Mingzhu; Li, Rui; Li, Yongdong; Lv, Donghui; Shao, Shuai
Abstract: This paper presents the development of a novel megavolt-class equal breakdown probability (EBP) multi-stage self-discharge gas switch for high power microwave generation with low breakdown jitter and high reliability. With the joint distribution of breakdown probability for 'n' identical stages of EBP gas switch, the advantages of diminishing the breakdown jitter and omitting the complex breakdown order problem are hence disclosed in considerable details with the aid of probability computation method. Based on theoretical analysis, a 5 stages 1-MV EBP multi-stage gas switch is designed in which periodic cog profile cathode is proposed to further decrease the breakdown jitter. The performances of EBP switch are tested at the repetition rate of 1, 10, 20, 50 Hz over 1000 successive pulses with breakdown jitter as low as 2.7%, energy efficiency as high as 90% and pulse rising time as low as 5 ns. The overall performance of EBP gas switch shows great potential in compact and reliable high power microwave generating system.